Postpartum acute stress disorder symptoms, social support, and quality of couple’s relationship associations with childbirth PTSD - Handelzalts, Jonathan E.; Kalfon-Hakhmigari, Maor; Raichin, Adi; Peled, Yoav (Frontiers in Psychiatry, 2024)
Background We aimed to examine the hypothesized negative associations between childbirth post-traumatic stress disorder (PTSD) symptoms (using the two-factor model of birth-related and general symptoms), social support, and a couple’s relationship quality at 8–12 weeks postpartum. This analysis considered the longitudinal positive shared variance with acute stress disorder (ASD) symptoms measured shortly after birth, while accounting for obstetric and demographic variables. Methods Participants included 246 mothers who gave birth at the maternity ward of a tertiary healthcare center. Self-report questionnaires were used 1–4 days postpartum (T1): Demographic information, the Birth Satisfaction Scale-Revised (BSS-R), and the National Stressful Events Survey Acute Stress Disorder Short Scale (NSESSS). At T2 (8–12 weeks postpartum), the Multidimensional Scale of Perceived Social Support (MSPSS), the Dyadic Adjustment Scale (DAS-7), and the City Birth Trauma Scale (BiTS). Results In partial support of our hypotheses, three hierarchical regression analyses revealed a significant positive contribution of ASD symptoms to childbirth PTSD general symptoms (β = .33, p <.001) and the total score (β = .29, p <.001), but not to birth-related symptoms. Social support (β = -.21, p = .003) and the quality of the couple’s relationship (β=-.20, p = .003) showed negative associations with the BiTS general symptoms. Conclusion Our study enhances understanding of the shared variance between childbirth ASD and PTSD, supporting the factor structure of general and birth-related symptoms as different aspects of childbirth PTSD and highlighting the negative association of social support and the quality of a couple’s relationship with PTSD general symptoms, suggesting potential avenues for targeted interventions.